Imprensa e forças armadas no Brasil pós-guerra fria (1995-1998). - Albertini, Lauriani Porto (Universidade Federal de São Carlos, 2006)
With the end of the Military Regime, the fall of the Soviet Union and the rise of the neoliberalism, the relationship between media and the military by the way, already tense in the authoritarian Brazil was expressed in a diffused and confused way. Somehow, we can say that there are two points of view on the military problem: one, a Liberal, economic emphasized; other, a Realistic or Conservative, with emphasis in the national security). Nevertheless, both visions have influenced and may determine the kind of relationship that some parts of the press had with the Armed Forces in Brazil, in the years of 1995 to 1998. The research focus on the systematic analysis of Folha de S. Paulo and O Estado de S. Paulo articles and editorials. In that way, we suggest that Folha, influenced by the liberal view, represents itself more critic to the military, showing to the society a series of hostile reflections upon the military corporation. At the same time, O Estado de S. Paulo (influenced by a conservative point of view) presents itself on the support of keeping a modern Armed Forces to national defense.
Keywords: Forças armadas; Imprensa braileira; Neoliberalismo; Armed Forces; Press; Neoliberalism; CIENCIAS SOCIAIS APLICADAS